Interplay Between Stress and Reproduction: Novel Epigenetic Markers in Response to Shearing Patterns in Australian Merino Sheep (Ovis aries) - Narayan, Edward; Sawyer, Gregory; Fox, Dylan; Smith, Ryan; Tilbrook, Alan (Frontiers in Veterinary Science, 2022)
In this study, we determined the effect(s) of early shearing on Australian Merino ewes (Ovis aries) and their lambs. To test this research question, we used a suite of field and laboratory methods including GPS collars, wool cortisol and epigenetic change between ewes and lambs identified using Illumina NovaSeq RRBS. Single shorn ewes (n =24) were kept on their full fleece throughout the entire gestation period while twice (early) shorn ewes (n =24) had their wool shorn pre-joining. Top-knot wool sample was taken from ewes during pre-joining, day 50 (mid-gestation) and day 90 (late gestation). Ewes were pregnancy scanned at mid-gestation to determine whether they were early or late parturition (this confirmation is provided by the pregnancy scanner based on fetus size). Ear-tissue was taken from ewes at day 50 (mid-gestation) and from lambs at lamb marking for DNA analysis. Results showed that twice or early shorn ewes grazed 10% higher and maintained stronger body condition than once shorn ewes. Wool cortisol levels were also significantly lower in the early shorn ewes between mid- and late gestation. Lambs bred from twice shorn ewes had on average better visual wool quality parameters in terms of micron, spin finesses and curvature. For the DNA methylation results, when comparing a group of once sheared with twice sheared ewes, we have discovered one locus (Chr20:50404014) that was significantly differentially methylated (FDR = 0.005). This locus is upstream of a protein coding gene (ENSOARG00000002778.1), which shows similarities to the forkhead box C1 (FOXC1) mRNA using BLAST searches. To further our understanding of the potential interaction between pregnancy status and shearing frequency of the ewes we performed further differential methylation analysis using a combination of shearing treatment and pregnancy scanning status. We discovered that 36 gene loci were significantly modulated either between different shearing treatments or late vs early pregnancy status of ewes. This result suggests that maternal pregnancy and nutritional status during gestation influences DNA methylation. We further investigated DNA methylation in lambs and identified 16 annotated gene loci that showed epigenetic modulation as a result of being born from an early or late-stage pregnancy.